Freeze fresh meal prep : 160 meal starters and make-ahead dishes for the freezer - Schmidt, Crystal (Storey Publishing, 2026)
"Crystal Schmidt, best-selling author of Freeze Fresh, offers a unique approach to meal prep, with 160 recipes for complete meals as well as meal starters-dishes that can be partially prepared and frozen, then combined with pantry ingredients to make a complete meal. Using garden fresh vegetables and fruits, Schmidt offers original recipes for soup starters, sauces and dips, side dishes, beverage starters, baked goods, frozen treats, pie or cobbler fillings, and freezer jams"-- Provided by publisher.